2016
DOI: 10.1038/icb.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Impaired activation of ALS monocytes by exosomes

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal and progressive neurodegenerative disease affecting predominantly motor neurons in the spinal cord and motor cortex. Neurodegeneration in ALS is accompanied by a well-characterized neuroinflammatory reaction within the central nervous system and, as described more recently, cells of the peripheral immune system. Particularly monocytes have been implicated in ALS pathogenesis. Exosomes are membrane-enclosed vesicles secreted by various cell types with a diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Several studies have reported the activation of monocytes in the peripheral blood of ALS patients ( 100 ), as well as the increased invasion of peripheral monocytes into the spinal cord of ALS patients and mice ( 101 , 102 ), which contributed to MN loss. Activated monocytes from ALS patients exhibited decelerated phagocytosis, altered adhesion behavior, and impaired proinflammatory cytokine secretion ( 102 , 103 ). A recent study revealed 233 differentially expressed genes in ALS monocytes.…”
Section: Neuroinflammation In Als: Perspective On Cellular Basismentioning
confidence: 99%
“…Several studies have reported the activation of monocytes in the peripheral blood of ALS patients ( 100 ), as well as the increased invasion of peripheral monocytes into the spinal cord of ALS patients and mice ( 101 , 102 ), which contributed to MN loss. Activated monocytes from ALS patients exhibited decelerated phagocytosis, altered adhesion behavior, and impaired proinflammatory cytokine secretion ( 102 , 103 ). A recent study revealed 233 differentially expressed genes in ALS monocytes.…”
Section: Neuroinflammation In Als: Perspective On Cellular Basismentioning
confidence: 99%
“…Another study found that there was increased expression of HLA-DR on CD14 + monocytes in ALS and this correlated with the rate of disease progression (58). Another study used exosomes to activate monocytes, and found that monocytes from ALS patients were less responsive than those from healthy individuals (109). ALS monocytes are less responsive to purinergic stimulation than those from controls (110).…”
Section: Monocyte Numbers and Proportionsmentioning
confidence: 99%
“…This fatal and progressive neurodegenerative disease affects motor neurons (MNs) in the spinal cord and motor cortex. However, neuroinflammation and peripheral immune system activation were shown to accompany ALS neurodegeneration (Zondler et al, 2017). The underlying mechanisms are still unknown, but seem to involve multiple neural cell dysfunctional processes and complex multisystem deregulation, what turns difficult the identification of specific targets and the development of successful therapies.…”
Section: Introductionmentioning
confidence: 99%